2005
DOI: 10.1002/we.182
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of a few statistical models for making quantile wind power forecasts

Abstract: During the last few years, probabilistic wind power forecasts have received increasing attention because of their assumed value in decision‐making processes. In the current article, three statistical methods are described and several models based on these are compared. The statistical methods are local quantile regression, a local Gaussian model and the Nadaraya–Watson estimator for conditional cumulative distribution functions. The focus is on quantile forecasts, since these often provide the required type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 9 publications
0
50
0
Order By: Relevance
“…The latter ones are the most common and utilized in practice today, even though the use of prediction risk indices also comprises a promising alternative (or complementary) approach [4]. Probabilistic predictions can be either derived from meteorological ensembles [5], based on physical considerations [6], or finally produced from one of the numerous statistical methods that have appeared in the literature, see [4,7,8,9, 10] among others. Their aim is to give more information on the random variable P t+k than the simple summary statistics given by a point forecast.…”
Section: Introductionmentioning
confidence: 99%
“…The latter ones are the most common and utilized in practice today, even though the use of prediction risk indices also comprises a promising alternative (or complementary) approach [4]. Probabilistic predictions can be either derived from meteorological ensembles [5], based on physical considerations [6], or finally produced from one of the numerous statistical methods that have appeared in the literature, see [4,7,8,9, 10] among others. Their aim is to give more information on the random variable P t+k than the simple summary statistics given by a point forecast.…”
Section: Introductionmentioning
confidence: 99%
“…As wind-power generation is a nonlinear and bounded process, predictive densities may be highly skewed and with heavy tails (Lange, 2005), and hence be difficult to model accurately with known parametric families of density functions (see the discussion by Pinson, 2006). This has motivated the development of a large number of non-parametric methods for wind-power density forecasting, based on statistical methods and/or ensemble forecasts (see Bremnes, 2006;Møller, et al, 2008;Nielsen, et al, 2006;Pinson and Madsen, 2009a, among others).…”
Section: Application To the Reliability Assessment Of Density Forecasmentioning
confidence: 99%
“…Normalized prediction errors have been considered in this paper for both load and wind power forecasting, as described in equation (3). Thus, the errors take into account any loading or installed wind power capacity of the power system under study.…”
Section: Lw T L T W Tmentioning
confidence: 99%
“…Many efforts have been presented in the technical literature for wind power forecasting (wpf) in power systems, [1][2][3][4][5][6][7] but few of them have been used for autonomous power systems. 7,8 Recent studies [9][10][11][12][13][14] have shown that improving wpf has signifi cant economic savings for both utilities and the wind park owners participating in the energy market.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation